The afterlife exploring the application of book design on an interactive publication about Philippine pre-hispanic burial archaeology for secondary school students ages 13-15 - Cura, Liam Andrew E.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines Diliman, 2016)
The study of archaeology serves as a gateway to the past. Written history only goes so far and some parts of the world have been a mystery to us for centuries. Archaeology, however, is able to access a time before the written record and allows archaeologists to know more about who we are and where we come from. This sort of information becomes very important in history, culture and heritage education. Sadly, schools in the Philippines generally haven't integrated archaeology into the new K-12 curriculum. Many archaeologists believe that the study of archaeology should be made available to the public, especially in schools. Publications and programs that revolve around archaeology are popular in places like the US and the UK. With a rich background in material culture and archaeological artifacts, the Philippine public can benefit greatly from such channels of information. This study aims to make archaeology accessible to the public primarily through the use of an interactive publication, and secondarily, through a marketing campaign that aims to involve the younger public in matters of archaeology, beginning with teenage students ages 13-15. This study hopes to shed light on the relationship between archaeology and the public and show that there are many possibilities for visual communicators to share this amazing field of study with the very people that the study is all about : us Filipinos.
Thesis (Bachelor in Fine Arts major in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 207-208.
Keywords: Human remains (Archaeology) -- Philippines; Burial; Book design